Design of Low-Cost Full W-Band 8th Harmonic Mixers for Frequency Extension of Spectrum Analyzer - Jian Guo; Kaiyi Zang; Zihan Zhang; Liang Zhao; Jie Xu; Zhengbin Xu (IET Circuits, Devices and Systems)
High-order harmonic mixer is popular for frequency extension of spectrum analyzer (SA) from microwave to millimeter-wave or even terahertz band. The manufactures of SA usually offer expensive harmonic mixers where frequency extension is needed. In this work, low-cost designs of 2-port and 3-port W-band 8th harmonic mixers covering 75–110 GHz are proposed, and design method of two port mixer without frequency diplexer to separate local oscillator (LO) and intermediate frequency (IF) signals are first presented. These two kinds of mixers are compatible with almost all the current SAs with frequency extension options, which provides LO for the external harmonic mixer. The mixers are designed with planar microstrip lines and antiparallel Schottky diodes. The circuit of 2-port mixer includes the input broadband bandpass filter, diodes, output lowpass filter, and matching circuits. As for 3-port mixer, only an extra diplexer is needed to separate the IF signal and LO signal. The diplexer is composed of a planar semi-lumped lowpass and a highpass filter. The planar circuits are easily fabricated with low-cost print circuit board process on polytetrafluoroethylene substrate. The measured conversion loss of 2-port 8th harmonic mixer is from 20 to 26 dB, and 23 to 28 dB for 3-port mixer at full W-band. The good measured results indicate the proposed mixers are simple and effective.